Communication support for reliable distributed computing - Birman, Kenneth P.; Joseph, Thomas A. (1986)
We describe a collection of communication primitives integrated with a mechanism for handling process failure and recovery. These primitives facilitate the implementation of fault-tolerant process groups, which can be used to provide distributed services in an environment subject to non-malicious crash failures.
Keywords: Fault-tolerant computing; Synchronization